Enhanced osteoinductivity of porous biphasic calcium phosphate ceramic beads with high content of strontium-incorporated calcium-deficient hydroxyapatite. Issue 41 (28th September 2018) - Deng, Yanglong; Liu, Minjun; Chen, Xuening; Wang, Menglu; Li, Xiangfeng; Xiao, Yumei; Zhang, Xingdong
Abstract : Further biomimicking natural bone and enhancing osteoinductivity to meet the requirements of regenerative medicine is the key development direction of biphasic calcium phosphate (BCP) ceramics. Abstract : Further biomimicking natural bone and enhancing osteoinductivity to meet the requirements of regenerative medicine is the key development direction of biphasic calcium phosphate (BCP) ceramics. Bone mineral is a kind of Ca-deficient hydroxyapatite (CDHA) with many kinds of trace ions incorporated; however, little is actually known regarding the incorporation of trace ions in CDHA, and trace-ions-incorporated CDHA in BCP ceramics has seldom been studied. The present study introduces an effective approach to fabricate porous BCP ceramic beads with a high content of strontium (Sr)-incorporated CDHA (BCP-Sr), and investigated its biological performance, especially with regard to osteoinductivity. The obtained BCP-Sr possessed a good spherical shape, interconnected pore structure, and a high content of Sr-incorporated CDHA phase. Compared to the commercial BCP ceramic irregular granules (BAM® P2040, BCP-C), BCP-Sr had more micropores, relatively faster degradation, better bone-like apatite formation, higher protein adsorption abilities, and was more likely to promote the related osteogenic genes and protein expressions of BMSCs. Further in vivo canine intramuscular implantation confirmed that BCP-Sr had higher osteoinductivity than BCP-C. Collectively, the enhanced osteoinductivity of porous BCP ceramic beads by introducing a high content of Sr-incorporated CDHA has significant implications for designing highly bioactive BCP ceramics for applying in regenerative medicine.